Roots of urban forest conservation behaviors: Discovering determinants of citizens’ attitudes - Rahim Maleknia (Environmental and Sustainability Indicators)
Urban forests play a vital role in promoting sustainable cities by providing ecological, social, and health benefits. Despite their significance, the psychological factors influencing citizens’ attitudes toward urban forest conservation remain insufficiently explored. Addressing this research gap, this study investigates the cognitive, emotional, and experiential determinants of conservation attitudes among urban forest visitors in Tehran, capital of Iran. Drawing on a comprehensive theoretical framework, seven key predictors were examined: perceived benefits, ecological worldview, place attachment, nature connectedness, environmental concern, environmental knowledge, and media literacy. Using structural equation modeling to analyze data, the findings of research revealed that perceived benefits (ƛ = 0.317) exert the strongest influence on attitudes, highlighting the critical role of recognizing urban forests' advantages. Other significant predictors include ecological worldview (ƛ = 0.270), place attachment (ƛ = 0.199), and nature connectedness (ƛ = 0.133), emphasizing the importance of emotional connections to nature and urban green spaces. Additionally, environmental concern (ƛ = 0.166), environmental knowledge (ƛ = 0.104), and media literacy (ƛ = 0.106) demonstrated significant contributions to attitude formation via cognitive and affective pathways. The proposed model explains 79.6 % of the variance in attitudes, demonstrating the robustness of the proposed framework. These findings advocate for integrating cognitive, emotional, and experiential strategies to enhance public engagement and support for urban forest conservation. Practical implications suggest that urban planners, policymakers, and forest managers should highlight the benefits of urban forests, foster emotional bonds with nature, and promote media literacy and environmental knowledge through public engagement initiatives. By addressing cognitive and emotional dimensions, this study offers critical insights to enhance public support for urban forest conservation.